Effect of a health claim on consumer acceptance of milk-based dessert containing omega-3 (Research, Society and Development, 2021)
This study was to evaluate the influence of information on the addition of omega-3 and its health benefits in the acceptance of dairy dessert. The hedonic thresholds methodology was applied in two trials: blind and open-label. In the blind trial, no information was provided to consumers regarding the formulation of the flans. In the open-label trial, consumers received the information on the addition of omega-3 and its health benefits. The value of compromised acceptance threshold (CAT) was not influenced by the information on the addition of omega-3 and its health benefits. However, there was a high increase in the value of hedonic rejection threshold (HRT) when the consumers were informed of the benefits of omega-3, and it was possible to increase the addition of the compound in the flans by up to 21.03% without causing product rejection, confirming the positive effect of information on health benefits in accptance.